EXPLANATION OF THE PROBLEM OF PERIODICATION OF THE HISTORY OF UZBEKISTAN (Conferencea, 2024)
In this work, great attention is paid to the issue of studying the history of Uzbekistan divided into periods. Brief information about the practical work being carried out in the country was given, their essence and prospects were shown.